The genus Asuridia Hampson, 1900 in Taiwan, with descriptions of two new species (Erebidae, Arctiinae, Lithosiini) - Wu, Shipher; Fu, Chien-Ming (Zootaxa, 2013)
The lithosiine genus Asuridia Hampson, 1900 comprises seven described species from the Oriental region (Hampson 1900; Inoue 1988; Inoue and Kishida 1992; Fang 2000; Dubatolov et al. 2012). Its closest relative has been proposed to be Disasuridia Fang, 1991, based on the presence of a medial spur and absence of large cornuti on the aedeagus (Chang 1991; Kirti et al. 2013; the presence of spinose patches on the manica may be diagnostic for Asuridia). In Taiwan, only one endemic species, A. rubripennis Inoue, 1988, has been reported. However, the taxonomy of Asuridia remains incompletely understood, and we here review the Taiwanese fauna and describe two new species from Taiwan. Terminology in this paper follows Dubatolov et al. (2012), and institutional acronyms are as follows: BMNH, The Natural History Museum, London; ESRI, Taiwan Endemic Species Research Institute, Jiji, Nantou; NMNS National Museum of Natural Science, Taichung; NSYSU, National Sun Yat-Sen University, Kaohsiung; TFB, Taiwan Forestry Bureau, Taipei; TFRI, Insect Collection, Taiwan Forestry Research Institute, Taipei. Terminology in this paper follows Dubatolov et al. (2012).